Pengaruh WFH dan Transformational Leadership terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Mediasi - Imam Saroni; Aryana Satrya; Sri Listyarini (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
Due to the objectives of bureaucratic reform in all sectors and the Covid-19 pandemic situation, the Ministry of Finance of the Republic of Indonesia has 'accelerated' the implementation of the 'New Thinking of Working' (NTOW) in all organizational units, including the Regional Office of the Directorate of Finance of East Java Province, to improve employee performance, especially during the epidemic. NTOW should be accelerated. Previous research has shown that many work-from-home (WFH) implementations and transformational leadership styles can improve Employee Performance. In this case, researchers used online methods and relevant methods. Using online methods and in-person interviews with HR managers of the units, a survey of 152 employees within FinanceGov was conducted [A1] [A2] The purpose of this study was to analyze the extent to which the impact of work-from-home (WFH) and transformational leadership styles, mediated by job satisfaction, can improve employee performance through mediating job satisfaction. Performance through the mediation of job satisfaction. This study utilizes Structural Equation Modeling (SEM) through the Partial Least Squares (PLS) approach, facilitated by the SMARTPLS software. The results of this study indicate that Working at Home (WFH) and Transformational Leadership Style have an effect on Employee Performance and Job Satisfaction acts as a mediating variable that strengthens the impact of Working at Home (WFH) and Transformational Leadership Style on Employee Performance. Based on these findings, this study recommends the establishment of a more transparent and equitable allocation system for WFO/WFH to provide soft skills for direct leaders to be role models for employees, and to provide virtual capacity building to improve employee performance.